Guidelines for Internalizing Thai Values of National Council for Peace and Order through Buddhist Refinement - Maimun , Phramaha Devit; Madiloggovit , Charoonsri (Journal of Education Studies, Chulalongkorn University, 2020)
This research is aimed to analyze the results of values and the factors from training on according to Buddhist way which in accordance with Thai value of National Council for Peace and Order (NCPO) and 2), to propose how to educate Thai values of National Council for Peace and Order through the way Buddhist refinement, the subjects consisted of 399 high school students, the experimental instrument consisted of survey and focus group reports has included of 12 Thai values measure and interview to analyze data from questionnaire by finding Frequency, Percentage, average, standard deviation (S.D), T-test and the data from the interview were content analysis. The study found: 1.) The results of overall values were quite high and were in line with 10 of the 12 NCPO Thai values. 2.) The relevant factors found were: (1.) Individual demographic attributes; (2.) Family factors, such as guiding and taking care of parents; (3.) Factors related to school were: 1.having teachers as role models, 2. school policies, 3. school spirit and student morale. 3.) The Guidelines for Internalizing Thai NCPO’s Thai Values has been presented through Buddhist refinement trainings and are (1.) activities should be age appropriate; (2.) schools should promote annual training and participation policies; (3.) Buddhist monks should be invited to teach and instruct students at school; (4.) schools should create an appropriate atmosphere for activities and training.